2023
DOI: 10.3390/jintelligence11060102
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence, Personality and Tolerance of Ambiguity

Abstract: In this study, 3836 adults completed a personality test (the HPTI) and a multidimensional intelligence test (GIA). Two prominent theories that link personality traits to intelligence (compensation and investment) were tested. There were more sex differences in the personality traits than in the IQ scores. Correlational and regression analyses results provided little evidence for either theory but pointed to the role of tolerance of ambiguity as a consistently significant, positive correlate of IQ at both the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…The binary logistic regression results suggested that only two traits were important. The first was Ambiguity Acceptance which has been shown to be related to a wide number of positive work-related behaviors (Cuppello et al, 2023a(Cuppello et al, , 2023bFurnham & Impellizzeri, 2021;Teodorescu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The binary logistic regression results suggested that only two traits were important. The first was Ambiguity Acceptance which has been shown to be related to a wide number of positive work-related behaviors (Cuppello et al, 2023a(Cuppello et al, , 2023bFurnham & Impellizzeri, 2021;Teodorescu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The inventory is 78 items in length. It has been used in a number of studies (Cuppello et al, 2023a(Cuppello et al, , 2023bFurnham & Treglown, 2018;Teodorescu et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypothesis 6: Ambiguity tolerance would be related to ML because of the studies that show it to be related to intelligence and also executive decision making (Cuppello et al, 2023;Furnham & Marks, 2013) Hypothesis 7: Risk approach (also labeled courage) would be related to ML because at the heart of successful leadership is the ability to evaluate and take well-calculated risks (Pendleton et al, 2021).…”
Section: Hypothesesmentioning
confidence: 99%